Endothelial Cell Junctional Adhesion Molecules: Role and Regulation of Expression in Inflammation. Issue 10 (October 2016) - Reglero-Real, Natalia; Colom, Bartomeu; Bodkin, Jennifer Victoria; Nourshargh, Sussan
Abstract : Endothelial cells line the lumen of all blood vessels and play a critical role in maintaining the barrier function of the vasculature. Sealing of the vessel wall between adjacent endothelial cells is facilitated by interactions involving junctionally expressed transmembrane proteins, including tight junctional molecules, such as members of the junctional adhesion molecule family, components of adherence junctions, such as VE-Cadherin, and other molecules, such as platelet endothelial cell adhesion molecule. Of importance, a growing body of evidence indicates that the expression of these molecules is regulated in a spatiotemporal manner during inflammation: responses that have significant implications for the barrier function of blood vessels against blood-borne macromolecules and transmigrating leukocytes. This review summarizes key aspects of our current understanding of the dynamics and mechanisms that regulate the expression of endothelial cells junctional molecules during inflammation and discusses the associated functional implications of such events in acute and chronic scenarios.